STABILITY AND CONTROLABILITY ANALYSIS ON LINEARIZED DYNAMIC SYSTEM EQUATION OF MOTION OF LSU 05-NG USING KALMAN RANK CONDITION METHOD - Septiyana, Angga; Hidayat, Kurnia; Rizaldi, Ardian; Suseno, Prasetyo Ardi Probo; Jayanti, Eries Bagita; Atmasari, Novita; Ramadiansyah, M. Luthfi; Ramadhan, Redha Akbar (BRIN Publishing, 2020)
This paper discusses the stability, control and observation of the dynamic system of the Lapan Surveillance UAV 05-NG (LSU 05-NG) aircraft equation. This analysis is important to determine the performance of aircraft when carrying out missions such as photography, surveillance, observation and as a scientific platform to test communication based on satellite. Before analyzing the dynamic system, first arranged equations of motion of the plane which includes the force equation, moment equation and kinematics equation. The equation of motion of the aircraft obtained by the equation of motion of the longitudinal and lateral directional dimensions. Each of these equations of motion will be linearized to obtain state space conditions. In this state space, A, B and C is linear matrices will be obtained in the time domain. The results of the analysis of matrices A, B and C show that the dynamic system in the LSU 05-NG motion equation is a stable system on the longitudinal dimension but on the lateral dimension directional on the unstable spiral mode. As for the analysis of the control of both the longitudinal and lateral directional dimensions, the results show that the system is controlled.